Construção e avaliação de uma abordagem para apoiar a compreensão e a manutenção de software baseada em mídias dinâmicas - Santos, Anne Caroline Melo (2020)
Context: Software Engineering (SE) has used textual documentation to represent the user requirements. For some people, textual descriptions may not be enough to understand what needs to be developed, requiring the use of other means of visualization. Objective: This work aimed to propose and analyze a multimedia approach, to support the comprehension and maintenance of software, as an alternative to the traditional requirements documentation techniques, evaluating whether the use of the CodeMedia plug-in increases the effectiveness of understanding and maintaining systems. Method: Initially, a systematic mapping was carried out to identify the approaches that promoted the use of multimedia resources in Requirements Engineering, as a support in the process of comprehension and maintaining software. Finally, a controlled experiment was carried out in the industry to assess the efficiency and effectiveness of the proposed multimedia approach. Results: For the state of the art, a wide variety of approaches were identified that promoted the use of multimedia in RE, among them: TRECE, MURMER, Wiki System Multimedia, Storytelling, UTOPIA, as well as approaches without explicit names. With the execution of the experimental process, it became evident that the multimedia approach presented the best results, especially in terms of effectiveness and level of customer satisfaction. Regarding the average coding time and the level of comprehension of the code, the multimedia approach proved to be less efficient. Conclusion: After analyzing the state of the art, it was evidenced that there was a favorable consensus regarding the use of multimedia in RE. The selected studies have shown to be favorable to the adoption of multimedia to persist software requirements. With the experimental evaluation, it was found that the multimedia approach was more effective in terms of correct coding and level of customer satisfaction with the final product, making it an option to be considered for Survey, Registration, Validation and Verification of user requirements.